Bioactivities from Marine Algae of the Genus Gracilaria - de Almeida, Cynthia Layse F. (Molecular Diversity Preservation International (MDPI), 2011)
Seaweeds are an important source of bioactive metabolites for the pharmaceutical industry in drug development. Many of these compounds are used to treat diseases like cancer, acquired immune-deficiency syndrome (AIDS), inflammation, pain, arthritis, as well as viral, bacterial, and fungal infections. This paper offers a survey of the literature for Gracilaria algae extracts with biological activity, and identifies avenues for future research. Nineteen species of this genus that were tested for antibacterial, antiviral, antifungal, antihypertensive, cytotoxic, spermicidal, embriotoxic, and anti-inflammatory activities are cited from the 121 references consulted.